Biochemical basis of resistance in wheat against Karnal bunt caused by Tilletia indica - VINEET K. SHARMA, JASPAL KAUR and SUCHETA SHARMA, MANINDERJEET SINGH, RITU BALA* (Indian Phytopathology, 2017)
The biochemical basis of Karnal bunt resistance was evaluated in four resistant (ALDAN, CMH77.308, H567.71 and HP1531) and two susceptible (PBW343 and HD2967) genotypes. The parameters studied included total phenols and defense related enzymes (peroxidase, phenylalanine ammonia lyase and polyphenol oxidase). The level of total phenols and activity of the defense related enzymes was more in resistant as compared to the susceptible genotypes. However, there was variation within the resistant genotypes. Maximum level of total phenols was observed in CMH77.308 at 3 days after inoculation while maximum peroxidase activity was observed in H567.71 after 2 days of inoculation. The activity of polyphenol oxidase was highest after 3 days of inoculation in the resistant genotype HP1531 while maximum activity of phenylalanine ammonia lyase was observed in H567.71 after 3 days of inoculations.